EFEITO DO OCTADECILAMINA NAS PROPRIEDADES DAS BLENDAS DE POLI(METACRILATO DE METILA)/POLIESTIRENO - Jacqueline S. Sousa; Bruna de Oliveira; Thaises B. S. de Lima; Tiago F. A. Santos; Fábio O. S. Ribeiro; Alyne R. de Araújo; Elmo S. Araújo; Renata F. S. Santos; Kátia A. S. Aquino (Química Nova)
Blends of poly(methyl methacrylate)/polystyrene (PMMA/PS) in compositions 95/05 and 90/10, with and without the surfactant octadecylamine (ODA), were studied. Analysis of the results obtained by a viscosimetric method using the classical models, Fourier Transform Infrared Spectroscopy (FTIR), and refractive index showed that the blends are immiscible. However, viscosimetric analysis of miscibility using the cluster model showed that polymeric aggregates are formed in blends with ODA. Such aggregates, which possibly modified the distribution of polymer chains in the system, had an essential impact on the properties of blends with ODA, making a less rigid material with lower glass transition temperature (Tg), lower optical gap energy, and higher refractive index.